Structuralism and semiotics - Hawkes, Terence (Methuen, 1977)
Intended for those with no prior knowledege of the subject, this book discuses the nature and development of structure and semiotics. It answers questions raised by the whole 'science of signs' considering what 'reading' and 'writing' involves.